2021
DOI: 10.3389/fphar.2021.635165
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Considerations in Relation to Calcineurin Usage in Elderly Kidney Transplant Recipients

Abstract: This review summarizes how possible age-related changes in tacrolimus and cyclosporine pharmacokinetics and pharmacodynamics may influence drug dosing and monitoring in the elderly, and highlights how micro-sampling may be useful in this cohort in the future. Advancing biological age leads to physiological changes that can affect drug absorption, distribution, metabolism and excretion, as well as immune system responsiveness. Some studies have shown that elderly recipients may have higher dose-adjusted exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…CsA has a narrow therapeutic window and displays broad pharmacokinetic variability (Cossart et al, 2021). CYP3A4 is the Frontiers in Pharmacology frontiersin.org main metabolic pathway involved in the disposition of CsA.…”
Section: Discussionmentioning
confidence: 99%
“…CsA has a narrow therapeutic window and displays broad pharmacokinetic variability (Cossart et al, 2021). CYP3A4 is the Frontiers in Pharmacology frontiersin.org main metabolic pathway involved in the disposition of CsA.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have explored the pharmacokinetics and pharmacodynamics of calcineurin inhibitors and have shown variable results on how PGx-directed dosing impacts clinical outcomes [ 11 , 12 ], to the best of our knowledge, there have not been any studies exploring how the PGx results may inform general medication management in patients after kidney transplant. Multiple studies showed an average number of prescribed medications for patients with end-stage renal disease between 10–12 [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%